Dissolution Threats and Legislative Bargaining - Becher, Michael; Christiansen, Flemming Juul (Wiley, 2014)
Chief executives in many parliamentary democracies have the power to dissolve the legislature. Despite a well-developed literature on the endogenous timing of parliamentary elections, political scientists know remarkably little about the strategic use of dissolution power to influence policymaking. To address this gap, we propose and empirically evaluate a theoretical model of legislative bargaining in the shadow of executive dissolution power. The model implies that the chief executive's public support and legislative strength, as well as the time until the next constitutionally mandated election, are important determinants of the use and effectiveness of dissolution threats in policymaking. Analyzing an original time-series data set from a multiparty parliamentary democracy, we find evidence in line with key empirical implications of the model.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas